Our plastic problem and how to solve it - Morath, Sarah J. (Cambridge : Cambridge University Press, 2022)
Plastic pollution is a global problem that defies a singular solution. Our Plastic Problem and How to Solve It considers plastic's harm to the environment, from its production to its disposal, and offers a spectrum of solutions that require action by local and federal governments, businesses and non-profits, and individuals. Using specific examples and case studies, the book describes the history and chemistry of plastic, illustrates its harms, and points toward specific legislation and policies to offer concrete solutions. Plastic pollution is ubiquitous and has impacts on soil, food, air, and water. To solve our plastic problem, collaboration across disciplines will be critical; innovations in science, law, and design will be essential. The book demonstrates the need to approach environmental problems from an interdisciplinary lens, and will benefit anyone interested in learning more about the harms and solutions associated with plastic pollution.
Title from publisher's bibliographic system (viewed on 18 Mar 2022).
Keywords: Plastics -- Environmental aspects; Plastic scrap